Allosterically switchable network orients β -flap in Clostridioides difficile toxins - Lauren M. Finn; Rebecca Cummer; Bastien Castagner; Bettina G. Keller (Proceedings of the National Academy of Sciences, 2025)
Allosteric proteins exhibit a functional response upon ligand binding far from the active site. Clostridioides difficile toxins use allosteric binding by the endogenous cofactor myo -inositol hexakisphosphate to orchestrate self-cleavage from within the target cell. This binding event induces a conformational shift, primarily effecting a lever-like β -flap region, with two known orientations. We uncovered a mechanism for this allosteric transition using extensive atomistic molecular dynamics simulations and computational and experimental mutagenesis. The mechanism relies on a switchable interaction network. The most prominent interaction pair is K600-E743, with K600 interactions explaining ∼70% of the allosteric effect. Rather than gradually morphing between two end states, the interaction network adopts two mutually exclusive configurations in the active and inactive state. Similar switchable networks may explain allostery more broadly. This mechanism in particular could aid in drug development targeting the C. difficile toxins autoproteolysis.